PENGARUH MEDIA SCRAPBOOK DALAM MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS XI SMA 1 SIMANJAYA - Risnawati; Ajuni Deva Triyana (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research aims to determine the effect of scrapbook media on students' skills in writing poetry at SMA 1 Simanjaya Sekaran. This research is quantitative research, this research focuses on students' skills in writing poetry. Research data was taken in June 2024. The type of research used was an experiment with a quantitative approach, where the resulting data will be in the form of numbers. From the data obtained, analysis was carried out using SPSS software. The research design used was a Quasi Experimental design with a nonequivalent control group design, there was a significant influence on providing treatment in the form of using scrapbook media on student learning outcomes in the poetry writing skills material at SMA 1 Simanjaya. Data was collected using test sheets as many as 43 students took the pretest and posttest, targeting students in class XI 1 and XI 2, SMA 1 Simanjaya, Siman Village, Kec. Now District Lamongan. The research data was then calculated using SPSS 16 to determine whether the data taken from one class had an effect on students or not. The results of the first research use pre-test data and the results of the second research use post-test data. From this data, researchers can conclude whether the results obtained from students' skills in writing poetry using scrapbook media